Energy saving and performance stability of silicon carbide reinforced aluminium composite automotive brake rotor - Maleque, Md. Abdul; Abdulmumin, Adebisi Adetayo (2013)
In this invention, lightweight composite brake rotor is fabricated using a stir casting method in order to investigate the performance stability in terms of temperature rise and hot spot generation on the brake rotor surface and comparison of actual braking test and simulation result. A mathematical model is also developed to predict the influence of weight reduction on energy saving of composite brake rotor. Composite light weight brake rotor showed 50 % weight reduction, having the density of 2.82 - 2.9 g/cc and hence, 19 % energy savings compared to cast iron brake rotor. Minimum hot spot zone generation was obtained on the multiple particle size silicon carbide reinforced aluminium composite brake rotor due to lower surface temperature rise compared to cast iron. The actual brake test and finite element simulation results of surface temperature rise showed a good agreement.